Clinical Profile, Management, and Outcome of Posterior Urethral Valves in Children - Experience from a Tertiary Care Hospital - Gali Divya; Vijay Kumar Kundal; Rajasekhar Addagatla; Ritesh Kumar; Sandeep Kumar Jaglan; Pinaki Ranjan Debnath; Atul Kumar Meena; Shalu Shah (Wolters Kluwer Medknow Publications, 2024)
Background: Posterior urethral valves (PUV) are the most common obstructive anomaly of the lower urinary tract in children. End-stage renal disease (ESRD) in 17% of the children is due to PUV. The present study helps know the spectrum of the disease, management options, and the outcome in these children. Methods: The present study is a descriptive type of study by review of medical records of all the children presented to the hospital from 2015 to 2019. Profile of PUV includes any abnormality in antenatal ultrasonography (USG), age at presentation, presenting complaints, general condition at the time of presentation, biochemical investigations like serum creatinine and electrolytes at admission, clinical progression during hospital stay and the type of intervention. Outcome variables studied were improvement in the stream and overall well-being of the child, renal function, recurrent urinary tract infections (UTIs). Follow-up period varied from 1 to 6 years. Results: A total of 73 patients were included in the study. The mean age of presentation was 3.4 years. The most common presenting complaints were poor urinary stream and dribbling of urine. Antenatal USG showed abnormality in 23 patients. Renal function was abnormal in 28 patients. Out of 73 patients, 51 underwent endoscopic ablation of valves, 19 underwent vesicostomy, and three patients underwent supravesical diversion. During the follow-up recurrent UTI was observed in 11 patients, 15 patients progressed to chronic kidney disease, and 15% of patients were hypertensive. Mortality in the present study was 4%. Conclusion: PUV includes a spectrum of diseases from mild form to lethal conditions. Early intervention by relieving obstruction may prevent or delay the ESRD; hence, timely intervention is necessary in these children.